Perspektif Jaringan Pertukaran Maritim terhadap Sumber-sumber Pangan di Pulau-pulau Kecil Kabupaten Wakatobi Sulawesi Tenggara - La Ode Rabani; Adhi Rahman Bani (SASDAYA: Gadjah Mada Journal of Humanities, 2020)
This article analyzes the sources of foods in small islands from the maritime exchange network perspective. The location of the research was a group of small islands in Southeast Sulawesi. This research found that resources of food in the small islands came from the other region as part of the process of exchanges maritime networks, especially from the Wallacean line connection and other main islands of Indonesia. Process and its form become local culinary, were other a part of the creative process, and the expression of its citizens. Some supporting tools for processing resources of food also identified as an invention from the local society have been fully health standards. To support that argument, the authors identifying the origins of food resources, processing, and preserving strategies. Knowledge about the food resources on the small islands contributes to the understanding of the globalization connections in small Islands, a wider world at the local level.